Two Cases of Symptomatic Elongated Styloid Process - Tanaka, Hiroshi; Okaue, Masahiro; Matsumoto, Mitsuhiko; Ozawa, Toshifumi; Shimoyama, Tetsuo; Hasegawa, Mitsuharu; Hori, Minoru (Journal of Nihon University School of Dentistry, 1995)
Two cases of elongated styloid process are reported. The first occurred in a 27-year-old man whose only complaint was pain when moving the jaw, and its differential diagnosis was comparatively simple. The second case occurred in a 33-year-old woman, for whose condition differential diagnosis was more difficult, as she presented many symptoms, including neuralgic pain in the face and neck, pain in the pharynx when swallowing, and pain in the region of the temporomandibular joint, radiating to the subauricular and submandibular regions. Following surgical shortening of the elongated styloid process through an intraoral approach, both patients' symptoms disappeared or were improved.